Flicka - Bello, Maria, 1967-; Lohman, Alison, 1979-; Kwanten, Ryan, 1976-; OHara, Mary.; William O. Van Arsdale, IV and Family Collection (Beverly Hills, Calif. : 20th Century Fox Home Entertainment, 2006)
Katy dreams of filling her fathers shoes by taking over their ranch, while her father wants better for her. When she finds and tries to tame a wild horse, she learns how alike she and this stallion truly are.
Based on the novel "My friend Flicka" by Mary OHara.
Originally released as a motion picture in 2006.
Special features include: music video "My little girl" by Tim McGraw; audio commentary by director Michael Mayer; trailers; deleted scenes; making-of featurette; bloopers; gag reel.
Keywords: Horses -- Training; Drama; Wild horse adoption -- United States; Drama; Ranch life -- United States; Drama; Animal films; Childrens films; Film adaptations